Transparencia en entidades públicas y su relación con la implementación de sistemas de gestión y normatividad anticorrupción (2021)
Measuring behaviors that alter public entities proper performance, such as corruption, is of vital importance to guide policies and concise actions that improve financial and organizational management, and the perception that the country's inhabitants have of them. This research seeks to establish whether management systems and anti-corruption regulations help entities to be more transparent and receive better ratings in the measurement of the National Transparency Index (ITN in Spanish). Forty petition rights were sent to different national entities to characterize those entities, establish trends, and determine the statistical correlation between the ITN, management systems and anti-corruption regulations. From the analysis of the information, it was concluded that the implementation of management systems and the application of anti-corruption regulations do not affect the INT results of the public entities analyzed.